Do taxes still affect earning persistence? - Ângela Pereira; Cláudia Pereira; Luís Gomes; Armindo Lima (Administrative Sciences, 2023)
While financial statements are the primary source of information about a firm, they tend to be under earnings management practices, namely to avoid paying tax. Therefore, we aim to examine whether taxes still affect earning persistence in an era of prevalent digital information. For that purpose, we use book-tax differences considering the deductible temporary differences and the taxable temporary differences. In addition, we analyze which of the two earnings components are more affected by taxes, specifically cash flow or accruals. We estimate econometric regressions using panel data to test our hypotheses. Through a sample of 421 small- and medium-sized (SME) Portuguese firms, between 2016 and 2020, we found empirical evidence that earning persistence tends to be lower when deductible temporary differences increase, while taxable temporary differences produce no statically significant effect. Furthermore, our results suggest that cash flow component increases more earning persistence than accruals. Therefore, deductible temporary difference may be an indicator of earnings management activities in these firms. These results are relevant, given the potential negative consequences of earnings management for the efficient decision making of stakeholders and even more because SMEs represent a substantial number of firms in European countries, particularly in Portugal.
Keywords: 350; accruals; book-tax differences; cash flows; earning persistence